Comparison of Feto-Maternal Outcomes of Conventional Method vs Reverse Breach Extraction Method in Delivering Deeply Engaged Foetal Head at Caesarean Section - Fatima, Rabia; Rafique, Amna; Mehr, Anum; Iqbal, Iram (Biological and Clinical Sciences Research Journal, 2025)
Cesarean section in the presence of a deeply impacted fetal head during the second stage of labour presents a significant obstetric challenge. It is associated with increased maternal and neonatal complications. Optimal surgical technique is crucial in minimizing adverse outcomes, yet the ideal extraction method remains a topic of debate. Objective: To compare the maternal and neonatal outcomes of the conventional (push) method versus the reverse breech extraction method during emergency cesarean sections performed for obstructed labour. Methods: This randomised controlled trial was conducted in the Department of Obstetrics and Gynaecology Unit II, Lahore General Hospital, Lahore, from August 2019 to March 2020. A total of 110 women undergoing emergency cesarean section for obstructed labour were enrolled and randomly assigned to either Group A (conventional method) or Group B (reverse breech extraction method) using the lottery method. Key outcomes assessed included maternal blood loss, extension of uterine incision, and neonatal intensive care unit (NICU) admission. Data were analysed using appropriate statistical tests, and a p-value of <0.05 was considered significant. Results: The mean age of participants in Group A was 27.22 ± 5.08 years, and in Group B was 28.36 ± 4.52 years. The reverse breech group demonstrated significantly lower mean blood loss (842.64 ± 123.14 mL) compared to the conventional group (p < 0.001). Extension of uterine incision occurred in 32.7% of cases in Group B versus a higher proportion in Group A (p = 0.004). NICU admission was also significantly less frequent in Group B (5.5%) compared to Group A (p < 0.05). Conclusion: The reverse breech extraction method during emergency cesarean section for obstructed labour is associated with reduced intraoperative blood loss, lower incidence of uterine incision extension, and fewer NICU admissions. This technique offers a safer alternative to the conventional method and should be considered in managing deeply impacted fetal heads during obstructed labour.